ANALYSING THE PROCESS OF VENDOR MANAGED INVENTORY - Pabbi, Jyoti (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
- Vendor Managed Inventory is a planning system in which the vendor is responsible for replenishment and management of inventory depending on the information shared between the supplier and buyer. The purpose of this paper is to investigate the literature on Vendor Managed Inventory and to segregate the analysis done by various researchers. The various research papers are classified into three categories and a conclusion is drawn about the future research Â Keywords - Vendor Managed Inventory, Inventory Models